Infarct Size, Shock, and Heart Failure: Does Reperfusion Strategy Matter in Early Presenting Patients With ST‐Segment Elevation Myocardial Infarction?. Issue 8 (August 2015) - Shavadia, Jay; Zheng, Yinggan; Dianati Maleki, Neda; Huber, Kurt; Halvorsen, Sigrun; Goldstein, Patrick; Gershlick, Anthony H.; Wilcox, Robert; Van de Werf, Frans; Armstrong, Paul W.
Abstract : Background: A pharmacoinvasive (PI) strategy for early presenting ST‐segment elevation myocardial infarction nominally reduced 30‐day cardiogenic shock and congestive heart failure compared with primary percutaneous coronary intervention (PPCI). We evaluated whether infarct size (IS) was related to this finding. Methods and Results: Using the peak cardiac biomarker in patients randomized to PI versus PPCI within the Strategic Reperfusion Early After Myocardial Infarction (STREAM) trial, IS was divided into 3 groups: small (≤2 times the upper limit normal [ULN]), medium (>2 to ≤5 times the upper limit normal) and large (>5 times the upper limit normal). The association between IS and 30‐day shock and congestive heart failure was subsequently examined. Data on 1701 of 1892 (89.9%) patients randomized to PI (n=853, 50.1%) versus PPCI (n=848, 49.9%) within STREAM were evaluated. A higher proportion of PPCI patients had a large IS (PI versus PPCI: small, 49.8% versus 50.2%; medium, 56.9% versus 43.1%; large, 48.4% versus 51.6%; P =0.035), despite comparable intergroup ischemic times for each reperfusion strategy. As IS increased, a parallel increment in shock and congestive heart failure occurred in both treatment arms, except for the small IS group. The difference in shock and congestive heart failure in the small IS group (4.4% versus 11.6%, P =0.026) in favor of PI likely relates to higher rates of aborted myocardial infarction with the PI strategy (72.7% versus 54.3%, P =0.005). After adjustment, a trend favoring PI persisted in this subgroup (relative risk 0.40, 95% CI 0.15 to 1.06, P =0.064); no difference in treatment‐related outcomes was evident in the other 2 groups. Conclusion: A PI strategy appears to alter the pattern of IS after ST‐segment elevation myocardial infarction, resulting in more medium and fewer large infarcts compared with PPCI. Despite a comparable number of small infarcts, PI patients in this group had more aborted myocardial infarctions and less 30‐day shock and congestive heart failure. Clinical Trial Registration: URL:http://ClinicalTrials.gov . Unique identifier: NCT00623623.